Timing of Neanderthal occupations in the southeastern margins of the Massif Central (France): A multi-method approach. (1st December 2021) - Richard, Maïlys; Pons-Branchu, Edwige; Genuite, Kim; Jaillet, Stéphane; Joannes-Boyau, Renaud; Wang, Ningsheng; Genty, Dominique; Cheng, Hai; Price, Gilbert J.; Pierre, Monique; Dapoigny, Arnaud; Falguères, Christophe; et al.
Abstract: The middle Rhône valley, located at the southeastern margins of the Massif Central in France, produced a large number of Middle Palaeolithic sites, most of which dated to the Middle and Late Pleistocene. Due to its position, connecting northern Europe and the Mediterranean basin, this corridor and the surrounding plateaus are of particular interest in the study of human cultural evolution, including the emergence of Middle Palaeolithic technology around 300, 000 years ago and its variability over time, as well as the subsistence and mobility strategies of Neanderthals. In the last 20 years, several research projects undertaken in this region allowed to revise key Middle Palaeolithic sequences. This work aims at synthesising previous and new chronological data obtained by using uranium-series of speleothems and bones, infrared stimulated luminescence of feldspar and electron spin resonance of tooth enamel and quartz. We review previous ages obtained in the area and present 43 new ages that are discussed together to propose a reliable spatiotemporal framework for Neanderthal occupations. We focus on major sites in the region: Payre, Ranc-Pointu 2, Baume Flandin, Abri du Maras, Grotte des Barasses II, Abri des Pêcheurs, Grotte du Figuier and Grotte de Saint-Marcel. They all provided significant information related to the biological and behavioural evolution of Neanderthal populations on the right bank of the Rhône valley. We present here the updated chronology for the Middle Palaeolithic of this area, ranging from ca. 300, 000 to 40, 000 years ago. Highlights: We review the Middle Palaeolithic chronology of the Middle Rhône valley in France. We provide 43 new ages using U-series, ESR and IRSL dating methods. The Levallois technology is documented as early as 300 ka. We show that Neanderthals continuously occupied the area from ca. 300 ka to 40 ka.